Digital Transformation of Civic Education Learning to Strengthen National Values and Character - Hidayatulloh, Muhammad Muslim; Sari, Dewi Ika; Winarno, Winarno (Riwayat: Educational Journal of History and Humanities, 2025)
This study analyzes the implementation of digital transformation in Civic Education (PPKn) to strengthen national values and character. Using a literature review and conceptual analysis approach, the study reveals that the integration of digital media such as Wordwall and Canva, along with the application of blended learning and flipped classroom methods, significantly enhances students' understanding of Pancasila values. The main findings of the study indicate that technology-based approaches not only increase student engagement but also facilitate the internalization of national values. However, the study also identifies challenges such as the spread of misinformation and digital distraction issues, which require strengthening digital literacy and more critical pedagogical approaches